2009
DOI: 10.1177/1086026609347188
|View full text |Cite
|
Sign up to set email alerts
|

The Other Side of the Diaspora: Race, Threat, and the Social Psychology of Evacuee Reception in Predominantly White Communities

Abstract: This article provides a social psychological framework for understanding the reception of Hurricane Katrina evacuees in predominantly White relocation communities. According to this framework, racial prejudice and perceptions of economic and social threat are likely to have an important influence on residents' reactions to the evacuees. In the "Katrina in my Community Study," the authors surveyed 532 residents from Colorado Springs, CO, Salt Lake City, UT, and San Antonio, TX-three cities that had African Amer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…For example, in a study of three receiving cities with considerable white populations, Hunt et al. () found that racial distance and subjective feelings of threat informed overall attitudes toward evacuees. They concluded that prejudice in white communities may frame and limit help to nonwhite evacuees, even if need is apparent.…”
Section: Framing the Victim: Empathy Versus Threatmentioning
confidence: 99%
See 3 more Smart Citations
“…For example, in a study of three receiving cities with considerable white populations, Hunt et al. () found that racial distance and subjective feelings of threat informed overall attitudes toward evacuees. They concluded that prejudice in white communities may frame and limit help to nonwhite evacuees, even if need is apparent.…”
Section: Framing the Victim: Empathy Versus Threatmentioning
confidence: 99%
“…To make sense of this possibility, Hunt et al. () distinguish between symbolic threat and realistic threat in their study of receiving communities shortly after Katrina. Symbolic threat, they explain, challenges established residents’ general values and beliefs, whereas realistic threat challenges immediate, objective well‐being.…”
Section: Framing the Victim: Empathy Versus Threatmentioning
confidence: 99%
See 2 more Smart Citations